Antimicrobial-resistant bacteria in international travelers. Issue 5 (October 2021) - Sridhar, Sushmita; Turbett, Sarah E.; Harris, Jason B.; LaRocque, Regina C.
Abstract : Purpose of review: Antimicrobial resistance (AMR) in bacteria poses a major risk to global public health, with many factors contributing to the observed increase in AMR. International travel is one recognized contributor. The purpose of this review is to summarize current knowledge regarding the acquisition, carriage and spread of AMR bacteria by international travelers. Recent findings: Recent studies have highlighted that travel is an important risk factor for the acquisition of AMR bacteria, with approximately 30% of studied travelers returning with an acquired AMR bacterium. Epidemiological studies have shown there are three major risk factors for acquisition: travel destination, antimicrobial usage and travelers' diarrhea (TD). Analyses have begun to illustrate the AMR genes that are acquired and spread by travelers, risk factors for acquisition and carriage of AMR bacteria, and local transmission of imported AMR organisms. Summary: International travel is a contributor to the acquisition and dissemination of AMR organisms globally. Efforts to reduce the burden of AMR organisms should include a focus on international travelers. Routine genomic surveillance would further elucidate the role of international travel in the global spread of AMR bacteria.